Penerapan Prinsip Syariah dalam Jual Beli: Perspektif Etika Bisnis dalam Ekonomi Islam - Aep Syaeful Millah; Rizka Rahmayani (Studia Economica : Jurnal Ekonomi Islam, 2026)
Sharia principles in buying and selling (muamalah) are fundamental principles in Islamic economics that aim to create balance and prevent exploitation. In practice, economic activities are often solely profit-oriented and do not fully reflect the applicable benefits as taught in Islam. This study aims to answer the main problem formulation, namely how the concept of maslahah can function as an evaluative instrument for assessing buying and selling practices from an Islamic economic perspective. The method used in this study is library research, a data collection technique by analyzing, reading, and studying all information relevant to the issue being studied or researched from e-books, manuscripts, books, journals, theses, and other similar materials. The results of this study indicate that business ethics in buying and selling practices are built on the principles of monotheism, justice, prophecy, mutual assistance, and results-oriented. These principles not only function as normative guidelines but also as controllers of market behavior so that economic transactions take place fairly, transparently, and free from exploitative practices. This study also found that the application of ethics such as honesty, fairness in pricing, and willingness between sellers and buyers can increase market trust, create transaction stability, and realize economic benefits for the community. This study presents a strengthening of the concept of maslahah as an analytical framework in buying and selling practices, thereby expanding the study of Islamic business ethics, which has focused more on formal legal aspects, towards an integrative approach between sharia principles, business ethics, and maqasid sharia